The reengineering revolution : - Hammer, Michael (Harper Business, 1995)
In The Reengineering Revolution, Michael Hammer and Steven Stanton build on this foundation to share with readers their experiences in successfully implementing reengineering in companies around the world. In an easy-reading, anecdotal style, the book offers behind-the-scenes stories of reengineering successes and failures; practical techniques for key aspects of reengineering, from breaking long standing assumptions to managing change; and insights into the new ways of thinking that reengineering requires